Implementasi Literasi Agama Untuk Meningkatkan Keterampilan Sosial Pada Siswa Sekolah Dasar - Endang Sri Maruti; Muhammad Hanif; Muhammad Rifai (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
The purpose of this study was to explain the implementation of religious literacy in elementary school students. Religious literacy needs to be taught to students so that they can live in the midst of this modern society. Religious literacy is one of the abilities to see and analyze the basic relationship between religion and social, political and cultural life through various perspectives. This research method is qualitative with a descriptive perspective. The results of the study indicate that religious literacy includes several things, including a basic understanding of the central texts that are the core of religion, history, and contemporary manifestations of religious traditions that are shaped according to certain social, political and cultural contexts. Religious literacy in addition to fostering interest in reading also trains students to be able to criticize sources of knowledge related to religion or the values ​​that they get in the form of text (books), oral, visual, and digital. Through a deep understanding of the sources of knowledge, one can choose various alternative values ​​and apply them as a form of self-actualization. Based on these results, it can be recommended that religious literacy is important to do from an early age, even from small things.